Holopothrips diversity—a Neotropical genus of gall-inducing insects (Thysanoptera, Phlaeothripidae) - Lindner, Mariana F.; Ferrari, Augusto; Mound, Laurence A.; Cavalleri, Adriano (Zootaxa, 2018)
The genus Holopothrips represents the main Neotropical group of thrips associated with plant galls, and several of the 36 currently described species are known to induce or invade galls of other organisms. The existence of several Holopothrips specimens in collections that do not belong to any of the already described species, allied to the absence of basic biological information for several species, such as host plants and habit, shows that the current knowledge on the genus is severely lacking. Here we start addressing these problems, by describing 24 new species: H. acrioris, H. atlanticus, H. bicolor, H. brevicapitatum, H. cardosoi, H. curiosus, H. flavisetis, H. graziae, H. inconspicuus, H. infestans, H. irregularis, H. johanseni, H. kaminskii, H. longihamus, H. longisetus, H. magnus, H. maiae, H. nigrisetis, H. nigrum, H. punctatus, H. reticulatus, H. singularis, H. spermathecus, H. varicolor. This study also includes information on galls for several species; an updated and illustrated key to species; and comments on the morphological diversity of the group. With that, we hope to lay the taxonomic and morphological bases for future studies in this group, focusing on its diversity, ecology and phylogenetic relationships.